An Overview of Neurocutaneous Syndrome (NCS) with a Special Reference to Symptomology - Omar M. Amin (Morgellon’s Disease and Neurocutaneous Syndrome (NCS): Cases and Recovery, 2021)
A detailed analysis of the clinical history of a random sample of 50 NCS patients (9 males, 41 females) is reported. Symptoms are classified into six categories, neurological, dermatological (including opportunistic skin infections), systemic, oral, allergic and general. The most common symptoms in each of these categories in the same order are pin prick and crawling sensations, skin lesions and sores, respiratory and bowel disturbances, gum disease, sensitivities to light, noise and mold, and fatigue and insomnia. Symptoms were relatively similar in both sexes. These results are tabulated and their biological foundation explained. The misdiagnosis of NCS by medical professionals is discussed. NCS symptoms in toothless patients and those on recreational drugs are described. Over 360 dental toxins are placed in four major categories and their mode of action explained. Incubation period varied between a few hours to 28 years. Our protocol for rehabilitation is included. All patients following and completing our rehabilitation protocol recovered.